Analisis Penggunaan Kakujoshi no (の) Pada Website Portal Berita NHK Japan Menggunakan Teknik Web Scraping - Mario Raditya Nugroho; Fadly Kurniawan; Muhammad Rahmat Maryadi; Rayhan ananda hafiz Pradipta; Humannisa Rubina Lestari (Universitas Diponegoro, 2025)
<p dir=